Lecturers’ Participation in Training and Development by Status as Capacity Building Mechanism for Quality Education: A Study of Nigerian Universities In The South-South Geo-Political Zone - Anho, Joseph Efe (NIU Journal of Social Sciences; Vol 4 No 4 (2018): KIU Journal of Social Sciences, Vol. 4 No. 4, December 2018, 2019)
This research report is a derivation from an earlier study by Anho, (2012), on the relationship between human resource development and lecturers productivity for quality assurance in Nigerian Universities. This report particularly looked at the level of lecturer’s participation in training and development by status as capacity building mechanism for quality education The research used the expost-facto design. The target population was all the lecturers in federal and state universities in the South-South geo-political zone of Nigeria as at 2009/2010 academic session. This made up of 4562 lecturers in the six states in the zone. The random sampling technique was used to obtain twenty percent (20%) of the population i.e. the sample figure is six hundred and eighty-seven (687), The main instrument used was the Anho (2012) adopted questionnaire on human resource development and lecturer’s productivity. The indices used are; number of conferences, seminars, workshops, and other short term or long-term courses attended, publications made before and after training, technical reports published, researches conducted and published among others. Particularly, lecturers pedagogical skills such as; quality of lectures delivered, quality of lecture, methods used, quality knowledge of human and learning psychology, quality questioning mechanism, etc. The Analysis of Variance (ANOVA) and the Scheffe’s test were used to test the hypothesis. The findings that emerged were that: there was a significant difference in the level of lecturer’s participation by status in training and development programme in Nigeria among the professorial cadre i.e. Professors/Associate Professors and Lecturers Il/Assistant Lecturers. Suggestions were offered, aimed at encouraging participation in training and developmental programmes, to keep them abreast of current knowledge of research and teaching and to reduce redundancy. Keywords : Participation, Capacity building, Human resources, Quality pedagogy, Publications, Training